(-1,-2) That is the answer to your question.
Substitution.
Here is an example.
Let x be equal to 3 and y equal to 3.
![x=3, y=3](https://tex.z-dn.net/?f=x%3D3%2C%20y%3D3)
From this we can conclude that the values of both x and y are equal to three therefore x and y have the same value and are equal.
![x\wedge y=3\Longrightarrow x=y](https://tex.z-dn.net/?f=x%5Cwedge%20y%3D3%5CLongrightarrow%20x%3Dy)
Here in your case we have:
![AB=1, BC=1 \\AB\wedge BC=1\Longrightarrow AB=BC](https://tex.z-dn.net/?f=%3C%2Fp%3E%3Cp%3EAB%3D1%2C%20BC%3D1%20%5C%5C%3C%2Fp%3E%3Cp%3EAB%5Cwedge%20BC%3D1%5CLongrightarrow%20AB%3DBC)
Hope this helps.
r3t40
C . no solution , that’s what I think :)
Answer: 3j +4
3(j)+ 3(2) = 3j+ 6 - 2 = 3j +4
Hope this helps